2011
DOI: 10.1007/s11255-011-9927-8
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive sleep apnea syndrome is related to the progression of chronic kidney disease

Abstract: In the light of the present study, we speculate that OSAS is an independent risk factor for the progression of chronic kidney disease, which is a growing health problem. Further randomized-multicenter prospective studies are warranted to evaluate this relationship.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
4

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(37 citation statements)
references
References 18 publications
0
33
0
4
Order By: Relevance
“…Recently, one study revealed that PSG variable, AHI and oxygen desaturation index, are independently associated with renal functional decline [9]. Data from Kanbay et al [28] also indicated that a significant decrease of GFR was detected in severe OSA patients, and they speculate that OSA is an independent risk factor of the progression of CKD.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, one study revealed that PSG variable, AHI and oxygen desaturation index, are independently associated with renal functional decline [9]. Data from Kanbay et al [28] also indicated that a significant decrease of GFR was detected in severe OSA patients, and they speculate that OSA is an independent risk factor of the progression of CKD.…”
Section: Discussionmentioning
confidence: 99%
“…Cross-sectional cohort studies have demonstrated a significant direct association between the severity of sleep apnea and the severity of renal dysfunction. [270][271][272][273][274][275][276] In addition, cohort studies of the longitudinal relationship between sleep apnea and kidney function show that apnea is independently associated with an increased risk of accelerated loss of kidney function. 277,278 Conversely, as kidney function declines, the prevalence of sleep apnea and nocturnal hypoxia increases.…”
Section: Repeated Episodes Of Acute Kidney Injurymentioning
confidence: 99%
“…We and others have performed crosssectional studies showing a significant negative association between the prevalence and/or severity of SDB and kidney function in the CKD population (1)(2)(3)(4)26). To date, there is only a single cohort study of the longitudinal relationship between SDB and kidney function, which showed that NH was a significant predictor of accelerated loss of kidney function (27).…”
Section: Introductionmentioning
confidence: 99%